1985
DOI: 10.1182/blood.v65.3.584.bloodjournal653584
|View full text |Cite
|
Sign up to set email alerts
|

Platelet kinetics in patients with idiopathic thrombocytopenic purpura and moderate thrombocytopenia

Abstract: We studied ten normal subjects and 20 patients with stable, untreated idiopathic thrombocytopenic purpura (ITP) and platelet counts in the range of 35,000 to 110,000/microL. The diagnosis was made by clinical criteria. Platelet-associated IgG was increased in all nine of the nine patients studied. Autologous platelets were labeled with chromium 51 and reinfused for measurement of mean cell life and platelet production rate. Mean cell life was calculated by two methods, weighted mean and multiple hit, with exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
1
40
0
2
Order By: Relevance
“…In randomized trials compared with placebo, each has been associated with a platelet count response in 60-70% of patients (Kuter et al, 2008;Bussel et al, 2009a). The remarkable success of TPO receptor agonists is consistent with earlier labelled autologous platelet studies that showed an impairment in platelet turnover in some patients with ITP (Stoll et al, 1985;Heyns et al, 1986;Ballem et al, 1987); yet is somewhat incongruous with the autoantibody theory because newly formed platelets would be expected to be rapidly destroyed. Thus, insufficient platelet production is another mechanism of thrombocytopenia in ITP.…”
Section: Relative Impairment In Platelet Productionmentioning
confidence: 86%
“…In randomized trials compared with placebo, each has been associated with a platelet count response in 60-70% of patients (Kuter et al, 2008;Bussel et al, 2009a). The remarkable success of TPO receptor agonists is consistent with earlier labelled autologous platelet studies that showed an impairment in platelet turnover in some patients with ITP (Stoll et al, 1985;Heyns et al, 1986;Ballem et al, 1987); yet is somewhat incongruous with the autoantibody theory because newly formed platelets would be expected to be rapidly destroyed. Thus, insufficient platelet production is another mechanism of thrombocytopenia in ITP.…”
Section: Relative Impairment In Platelet Productionmentioning
confidence: 86%
“…Increased platelet destruction, whether immunological (ITP) or consumptive (e.g., consumptive coagulopathy, haemolytic uremia syndrome, vasculitis), was characterized by accelerated platelet turnovers with corresponding increases in megakaryocyte mass. Table I shows platelet turnover data based on autologous thrombokinetic measurements from seven studies involving 218 patients with untreated ITP (Branehog, 1975;Branehog et al, 1975;Stoll et al, 1985;du P Heyns et al, 1986;Ballem et al, 1987;Isaka et al, 1990;Louwes et al, 1999). These results showed that increased platelet production rates are uncommon in ITP patients, with most exhibiting either depressed or normal platelet production rates.…”
Section: Platelet Turnover In Itp Patientsmentioning
confidence: 99%
“…With the introduction of 111 In, a radioisotope with characteristics more suitable for the study of platelet kinetics and distribution, the small numbers of autologous platelets in ITP could be adequately labelled and total-body scintigraphy performed (Thakur et al, 1976). Using 111 In it became evident that there was considerable heterogeneity in platelet turnover between patients, with a substantial proportion having platelet production within normal limits even though the mean cell life of platelets was significantly reduced compared with that in healthy subjects (Stoll et al, 1985;Heyns et al, 1986;Ballem et al, 1987). If platelet destruction were the only mechanism to cause thrombocytopenia, then platelet production would be expected to increase to offset low platelet counts.…”
Section: Antiplatelet Autoantibodies and Their Role In The Pathogenesmentioning
confidence: 99%